Improving Student Learning Outcomes in Mathematics Learning through Role Playing Method at MI Negeri 3 Banjarnegara - Hidayanti, Wahyu (MANDAILING GLOBAL EDUKASIA, 2025)
Implementation of Role Playing Method to Improve Student Learning Outcomes in Mathematics Subjects About Addition Story Problems for Class 2 of State Elementary School 3 Banjarnegara in the 2021-2022 academic year. The purpose of this study is as an effort to improve student learning outcomes that are still far from the learning success rate of at least 80%. In addition, this study was conducted as a Strengthening of Professional Skills as a Teacher. Based on the results achieved in the initial learning, only 63% of students were declared to have passed the learning process, while other students felt bored because the learning process with the lecture method turned out to be very monotonous and did not involve students, making them uninterested in understanding the lesson, which made the grades they achieved below the Minimum Completion Criteria (KKM). In the process of improving learning in the first cycle with the classical demonstration method, there was an increase in success, although the increase was not optimal, reaching 74%, but in the second cycle learning process with the Role Playing method in groups, success increased sharply to 85%. Thus, it can be ascertained that the way to teach students is by involving students directly, namely through the Role Playing method, this makes students motivated to improve their understanding, so that the learning outcomes achieved by students are at a level that meets the KKM.